2004
DOI: 10.1152/ajpgi.00375.2003
|View full text |Cite
|
Sign up to set email alerts
|

NOS2 deficiency increases intestinal metabolism both in nonstimulated and endotoxemic mice

Abstract: Animal studies have suggested that nitric oxide (NO) synthases (NOS) play a role in the regulation of protein metabolism in endotoxemia. We therefore investigated the role of inducible NOS (NOS2) on intestinal protein and neuronal NOS (NOS1) and endothelial NOS (NOS3) on amino acid metabolism. Three groups of mice were studied: 1) wild-type (WT), 2) NOS2 knockout (NOS2-KO), and 3) NOS2-KO + N(omega)-nitro-l-arginine methyl ester (NOS2-KO + l-NAME), both in nonstimulated and LPS-treated conditions. By infusion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 22 publications
0
7
0
1
Order By: Relevance
“…The discrepancy between whole body and renal metabolism might indicate that other organs, e.g., the gut, importantly downregulate their protein metabolism during early endotoxemia. In male C57BL6/J mice, we indeed observed a reduction in gut protein breakdown and synthesis (32).…”
Section: Renal Metabolism During Endotoxemiamentioning
confidence: 55%
See 1 more Smart Citation
“…The discrepancy between whole body and renal metabolism might indicate that other organs, e.g., the gut, importantly downregulate their protein metabolism during early endotoxemia. In male C57BL6/J mice, we indeed observed a reduction in gut protein breakdown and synthesis (32).…”
Section: Renal Metabolism During Endotoxemiamentioning
confidence: 55%
“…Moreover, the absence of an increase in plasma nitrate in NOS2 Ϫ/Ϫ mice may also be related to an effect on intestinal bacterial nitrate production in these mice. In addition, strain and sex differences seem to exist, since we observed, using the same experimental protocol, a 2.5-fold increase in systemic NO synthesis after LPS in Swiss mice (12) and a similar increase in male C57BL6/J mice (32).…”
Section: Renal Metabolism During Endotoxemiamentioning
confidence: 64%
“…LPS and endotoxin treatment in cell culture and rats respectively, induce Nos2 while decreasing Nos3 protein and mRNA expression [28–30]. Nos2 knockout mice show increased NOS1 and/or NOS3‐related activity, while in mice infected with Trypanosoma cruzi Ca 2+ ‐dependent (NOS1/NOS3) activity is decreased whereas Ca 2+ ‐independent (NOS2) activity increased [31,32]. Studies in endothelial cells demonstrated a decrease in NOS3 mRNA expression as a result of increased degradation [30,33].…”
Section: Discussionmentioning
confidence: 99%
“…In the mouse testes, there are two types of spermatogonium, undifferentiated and differentiating ones (2). Undifferentiated spermatogonia, also termed spermatogonial stem cells (SSCs), initiate spermatogenesis; they include type Asingle (As, isolated single cell), Apaired (Apr, chains of two cells) and Aaligned (Aal, chains of 4,8,16 or occasionally 32 cell) spermatogonia (3). Germ cell-specific protein Nanos2 is expressed in embryonic germ cells and has an important effect on survival and maintenance of germ cells (4)(5)(6).…”
Section: Introductionmentioning
confidence: 99%